Long-Term Effects of Zinc Deficiency and Zinc Supplementation on Developmental Seizure-Induced Brain Damage and the Underlying GPR39/ZnT-3 and MBP Expression in the Hippocampus - Chen, Ni-Na; Zhao, Dong-Jing; Sun, Yu-Xiao; Wang, Dan-Dan; Ni, Hong (Frontiers in Neuroscience, 2019)
We previously illustrated that long-term upregulated expression of ZnT-3 in the hippocampus of rats that underwent neonatal seizures was restored by pretreatment with a ketogenic diet (KD). It was recently demonstrated that upregulated expression of ZnT-3 was associated with increased concentrations of intracellular free zinc ions in an in vitro model of glutamate-induced hippocampal neuronal excitotoxic damage. However, there is still a lack of research on the effects of different concentrations of zinc in the diet on developmental convulsive brain injury. The aim of this study was to investigate the effects of different zinc concentrations in the diet on long-term neurobehavioral and seizure thresholds following lithium chloride-pilocarpine-induced developmental seizures. Sprague-Dawley rats (postnatal day 27, P27) were randomly assigned to one of six dietary groups for 4 weeks: normal zinc control group (Control group, 44 mg/kg Zn), Zn-deficient control group (ZD group, 2.7 mg/kg Zn), Zn-supplemented control group (ZS group, 246 mg/kg Zn), pilocarpine-induced seizure plus regular zinc diet group (SE group, 44 mg/kg Zn), seizure plus low-zinc diet group (SE+ZD group, 2.7 mg/kg Zn), and seizure plus high-zinc diet group (SE+ZS group, 246 mg/kg Zn). Novel object recognition and passive avoidance tests were performed on rats at P42 and P56. After routine seizure threshold detection and Timm staining procedures at P57, expression of GPR39, ZnT-3 and MBP were detected in the hippocampus by Western blot analysis. The results revealed that the Zinc-deficient diet for 4 weeks aggravated the long-term adverse effects of developmental seizures, evidenced by weight, cognition, seizure threshold and serum zinc concentrations, which were paralleled by expression changes in hippocampal GPR39 and ZnT-3. In contrast, zinc supplementation for 4 weeks significantly improved damage-related changes described above and rescued the abnormal expression of GPR39, ZnT-3 and MBP in the hippocampus. Similar alterations between the expression pattern of MBP and aberrant sprouting of mossy fibers in the hippocampus may indicate that sprouting is a pathological phenomenon related to the integrity of the neuronal plasma membrane.